The flight-to-quality effect: a copula-based analysis - Durand, Robert; Junker, M.; Szimayer, A. (Wiley-Blackwell Publishing Asia, 2010)
We derive and estimate a copula combining the features of the Frank and Gumbel copulas to analyse the relationship between equity and long-term bond returns. Our analysis of quarterly returns from 1952 to 2003 finds that, in general, there is a positive relationship between equity returns and bond returns. Inextreme situations, however, there is approximately a one-in-seven chance of a flight-to-quality effect where large negative equity returns are associated with large positive bond returns.